Modeling the energy consumption of potable water reuse schemes. (1st December 2021) - Tow, Emily W.; Hartman, Anna Letcher; Jaworowski, Aleksander; Zucker, Ines; Kum, Soyoon; AzadiAghdam, Mojtaba; Blatchley, Ernest R.; Achilli, Andrea; Gu, Han; Urper, Gulsum Melike; Warsinger, David M.
Highlights: Data and models were reviewed to estimate energy consumption in potable water reuse. Entire reuse schemes, both direct and indirect, require 1.2 to 2.1 kWh/m 3 . Lowest-energy options include non-RO indirect and RO-based direct potable reuse. Potable reuse requires much less energy than seawater desalination. Pipe network updates and high-permeability membranes would reduce energy use. Graphical abstract: Abstract: Potable reuse of municipal wastewater is often the lowest-energy option for increasing the availability of fresh water. However, limited data are available on the energy consumption of potable reuse facilities and schemes, and the many variables affecting energy consumption obscure the process of estimating energy requirements. By synthesizing available data and developing a simple model for the energy consumption of centralized potable reuse schemes, this study provides a framework for understanding when potable reuse is the lowest-energy option for augmenting water supply. The model is evaluated to determine a representative range for the specific electrical energy consumption of direct and indirect potable reuse schemes and compare potable reuse to other water supply augmentation options, such as seawater desalination. Finally, the model is used to identify the most promising avenues for further reducing the energy consumption of potable reuse, including encouraging direct potable reuse without additional drinking water treatment, avoiding reverse osmosis in indirect potable reuse when effluent quality allows it, updating pipe networks, or using more permeable membranes. Potable reuse already requires far less energy than seawater desalination and, with a few investments in energy efficiency, entire potable reuse schemes could operate with a specific electrical energy consumption of less than 1 kWh/m 3, showing the promise of potable reuse as a low-energy option for augmenting water supply.